Jørn Borup: Decolonising the Study of Religion - Cairns, Johannes (FINNISH SOC STUDY RELIGION, 2025)
Book review of Jørn Borup: Decolonising the Study of Religion: Who Owns Buddhism? Routledge Studies in Asian Religion and Philosophy. London: Routledge, 2023, 211 pp.